2013
DOI: 10.4172/2157-7412.1000199
|View full text |Cite
|
Sign up to set email alerts
|

EEG Correlates of Emotional Experience in Huntington’s Disease

Abstract: Recognizing negative emotions is impaired in Huntington's disease (HD), while the subjective emotional involvement in affective pictures images is not completely known in these patients. We aimed to further evaluate emotional reaction in early HD patients, by means of subjective arousal and valence rating and EEG changes induced by International Affective Pictures (IAPS).We recruited 16 consecutive genetically confirmed HD outpatients, and 16 sex and age matched controls. Eighty-four color slides, 28 pleasant,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The most frequently reported deficit is an impaired ability to identify emotions from pictures of actors posing with emotional facial expressions (e.g., Sprengelmeyer et al, 1996; Johnson et al, 2007; Labuschagne et al, 2013; Bora et al, 2016). Furthermore, many studies have found alterations in the self-reported experience of emotion in response to emotionally evocative stimuli (c.f., Mitchell et al, 2005; Paradiso et al, 2008; Eddy et al, 2011; Ille et al, 2011a; De Tommaso et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most frequently reported deficit is an impaired ability to identify emotions from pictures of actors posing with emotional facial expressions (e.g., Sprengelmeyer et al, 1996; Johnson et al, 2007; Labuschagne et al, 2013; Bora et al, 2016). Furthermore, many studies have found alterations in the self-reported experience of emotion in response to emotionally evocative stimuli (c.f., Mitchell et al, 2005; Paradiso et al, 2008; Eddy et al, 2011; Ille et al, 2011a; De Tommaso et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, when pictures of emotionally evocative scenes were used most studies found exaggerated emotional experiences in HD. Specifically, findings include exaggerated experiences of specific emotions, such as anger, fear, disgust, or happiness (Paradiso et al, 2008; Eddy et al, 2011; Ille et al, 2011a), and exaggerated experiences of arousal or valence (Paradiso et al, 2008; De Tommaso et al, 2013). Findings, however, also include a reduced experience of fear in HD (Eddy et al, 2011), as well as a lack of group differences when rating the experience of several emotions, including, disgust, happiness, or fear (Eddy et al, 2011; Ille et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation